Warm dense matter laboratory generation and diagnosis - Riley, David (IOP series in plasma physics, 2021)
This book provides an introductory overview of warm dense matter research for new postgraduate students entering the field. Author David Riley, based at the Centre for Plasma Physics at Queen's University Belfast, covers a broad range of topics with an emphasis on experimental techniques. The text begins with an introduction to the basic physics of warm dense matter and its important features, then moves on to discuss the principal techniques for creating warm dense matter and approaches to diagnosing it. Topics covered include the generation of warm dense matter via laser driven shocks and X-ray sources, explosives, gas guns and ion beams, as well as X-ray free electron lasers. Principal optical and X-ray diagnostics are also discussed. The book concludes with an overview of the large-scale facilities that are most commonly used for warm dense matter research and the technologies they employ. Part of IOP Series in Plasma Physics